The relationship between management's commitment and effective safety and health committees in Malaysia. Issue 2 (13th February 2017) - Farouk, Ummu Kolsome
Abstract : Purpose: The purpose of this paper is to study the relationship between management's commitment and effective occupational safety and health committees (OSHCs), which are a form of representative employee involvement in Malaysia. Design/methodology/approach: Using data from a survey of 231 manufacturing companies in Malaysia, the study empirically examines both passive and active management commitment and its relationships with the perceived effectiveness of OSHCs. Findings: Respondents to the survey, who were members of OSHCs, felt that both passive and active management commitments had significant, positive relationships with OSHCs' perceived effectiveness, with active management commitment having a stronger relationship with the dependent variable – the effectiveness of OSHCs. All three variables were perceived to be at the medium level, with active management commitment recording the lowest mean value. Research limitations/implications: The research is limited by the fact that it is cross-sectional. However, this allows its findings to be placed in the context of past research, underpinned by Malaysia's manufacturing sector and legislative framework. Practical implications: This paper provides suggestions for how the perceived effectiveness of OSHCs can be improved in the Malaysian context. Originality/value: This study conceptualises management's commitment in terms of passive and active commitment, given the context of the current legislative framework, and it addresses the relationships between both types of management commitment and the effectiveness of OSHCs, in the heretofore-unexamined Malaysian manufacturing context.